Forms of Politeness, Manners and Courtesy Rules in Children's Publications of Early Republican Period - Basboga Ozen, Sevcan (HACETTEPE UNIV, 2019)
In the process following the foundation of the Republic, the cadres who founded this regime attempted to formulate a new structure of state and society and aimed to construct a new individual according to the values and needs of the newly founded society. In this respect, the children who were supposed to found the new society, were raised to fortify the modem societal structure and the nation-state that the Republic intended to establish in accordance with the needs of the social structure and the idealized values of the Republic. In this context, the founding cadre of the Republic, acting in the direction of building a modem state and society structure, pioneered the civilization of the society and the related forms of politeness. This founding cadre, aimed the forms of politeness, manners and courtesy rules that the children of the republic should attain in the family life, to become an established set of behaviours by being reinforced in school and public life. In this study, the ways that children should behave at home, at school, on the street, on the road, in short, in any moment of daily life, requiring modem forms of politeness, as stated in children's periodicals published in the early Republican period and the forms of politeness literature of the era, have been investigated in detail. As a main source of this study, it has been focused on children's magazines which were popular among the children publications of the era. Although literature of late Ottoman and early Republic period focused on forms of politeness, manners and courtesy rules for only adults, this study aims to approach to the children who will be new members of the new society that the Republican administration wants to build by focusing on the children publications written specifically for them. Within this framework, Republican forms of politeness, manners and courtesy rules as one of the important efforts of the Republic to build a modem society and the continuity and discontinuity of forms of politeness in the process of late Ottoman modernization have also been problematized and the social and economic conditions and discourses of the presentation of Republican forms of politeness, manners and courtesy rules have been investigated.
Keywords: Modernization; Forms of Politeness; Manners and Courtesy Rules; Children; Children's Periodicals; History